TEMPERATURE AND LUMINOSITY EFFECT ON IN VITRO WHEAT PLANT REGENERATION - ORTOLAN, Dinara; SCHUELTER, Adilson; SCHUSTER, Ivan; VENDRUSCOLO, Eliane (Scientia Agraria, 2007)
In vitro calli cultivation conditions, light and temperature can influence the embryogenic and plant regeneration response. These two factors have not been studied in details in the literature, and its determination could contribute to the settlement of a more efficient tissue culture protocol. Immature embryos of wheat genotype CD104 were used as source of explants. The embryos were cultivated in MS medium with decreasing concentrations of 2,4-D forming three different phases: induction, maintenance and regeneration for a period of 21 days each one. Six different treatments were applied and, these differed exclusively by the induction phase, with two temperature conditions (4 °C and 25 oC) and two light conditions (photoperiod/darkness). Two different conditions of light were evaluated: 1) Constant photoperiod of 16/8 hrs (21 days) and 2) Completely darkness (10 days) and later transference of calli to light/photoperiod (16/8 hrs) in cultivation chamber (11 days). The data showed that the best results obtained for induction capacity, embryogenic and regeneration capacities (100% and 95%; 58,5% and 54,7%; 37,8% and 30,7%, respectively) were in 4 oC light and 4 oC darkness conditions, revealing that low temperature applied at the induction phase had a positive effect on calli regeneration. The treatment conditions of 25oC and light got the lowest values for calli induction (46%), embryogenic capacity (23,9%) and regeneration (23,9%), what can be inferred as an unfavorable condition to embryogenic establishment.